Determination of the cane honey point of panela under open evaporation in Colombia - Vladimir Antonio Rodríguez-Cediel; José Fernando Cárdenas-Barbosa; Orlando García-Hurtado (Visión Electrónica, 2021)
The granulated cane honey point of panela is given when the cane honey begins to solidify, based on the crystallographic properties of the honeys. In Colombia, the solidification point of panela is usually determined in an empirical way by panela manufacturers. In this study, we evaluated an automated method to determine the point of the panela cane honeys to produce a granulated panela in the regions of Colombia, in comparison with five possible scenarios that were previously tested, but choosing experimentally the best solution. The best method for determining the level was the saturation measurement by delta of the temperatures based on the graduation of the supersaturation of the sucrose presented as a line whose slope, and the value of Tan (q) indicate an index of the degree of supersaturation.